Mathematical Modeling of Thin-Layer Drying Behavior of Date Palm (Global Journal of Science Frontier Research, 2012)
The effect of microwave drying technique on drying kinetics of date palm was investigated. The results showed that the change of moisture ratio with drying time in the power density range from 4 to 9.5 W/g can be successfully described by Page model. Values of drying rate constant (k) were in the range of 0.052-0.142 (1/min) and the effective moisture diffusivities (D eff ) of date range palm from 2.72×10 -6 to 4.73×10 -6 (m 2 /s). The values of k and Deff increased with the increase of power density. The power density dependence of the effective diffusivity coefficient was expressed by an Arrhenius type relationship. Activation energy for the moisture diffusion was determined as 3.908 W/g.
Keywords: Mathematical modeling; moisture diffusivity; activation energy; date palm; microwave drying